Evaluation of Medicinal Plant Hepatotoxicity in Co-cultures of Hepatocytes and Monocytes - Bashar Saad (Evidence-Based Complementary and Alternative Medicine, 2006)
Non-parenchymal cells might play an important role in the modulation of xenobiotic metabolism in liver and its pharmacological and toxicological consequences. Therefore, the role of cell-to-cell interactions in herbal induced liver toxicity was investigated in monocultures of cells from the human hepatocyte cell line (HepG2) and in co-cultures of cells from the HepG2 cell line and cells from the human monocyte cell line (THP1). Cells were treated with various concentrations (1–500 µg ml−1) of extracts of Pistacia palaestina, Juglans regia and Quercus ithaburensis for 24 h. Extracts from Cleome droserifolia, a known toxic plant, were taken as positive control. In the co-culture system, toxic effects were observed after exposure to extracts of Pistacia palestina and C. droserifolia. These two extracts significantly reduced by cell viability as measured the MTT test and the LDH assay. Whereas in hepatocyte cultures, only extracts of C. droserifolia were found to affect the cell viability. The production levels of albumin from hepatocytes were not affected by treatment with plant extracts in both culture systems. It seems that the observed reduction in cell viability after exposure to extracts of P. palestina in co-cultures but not in monocultures is a result of monocyte-derived factors. The use of liver cell co-cultures is therefore a useful approach to investigate the influence of intercellular communication on xenobiotic metabolism in liver.